2018
DOI: 10.17576/jsm-2018-4706-23
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Biofortification of Fodder Sorghum with Zinc under Different Levels of Nitrogen

Abstract: Zinc (Zn) deficient soil prevails throughout the world and it has become the bottleneck in achieving production potential and quality of crops. The negligible use of micronutrients along with irregular use of macronutrients is practised for fodder production in Pakistan. Varying levels of zinc (0, 5, 10 and 15 kg ha -1 ) and nitrogen (0, 60, 120 and 180

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…According to Dambiwal et al (2017), a soil treatment of Zn @ 5 kg/ha with two foliar sprays of ZnSO 4 @ 0.5% in sorghum enhanced grain production by 3.24%.The sorghum plant requires extremely little Zn for proper development and production as well as physiological and metabolic functions. In comparison to control, Ahmad et al (2018) found that applying Zn @ 10 kg/ha increased green fodder output by 7.15% (2014) and 7.41% (2015).…”
Section: Nutrient Managementmentioning
confidence: 92%
“…According to Dambiwal et al (2017), a soil treatment of Zn @ 5 kg/ha with two foliar sprays of ZnSO 4 @ 0.5% in sorghum enhanced grain production by 3.24%.The sorghum plant requires extremely little Zn for proper development and production as well as physiological and metabolic functions. In comparison to control, Ahmad et al (2018) found that applying Zn @ 10 kg/ha increased green fodder output by 7.15% (2014) and 7.41% (2015).…”
Section: Nutrient Managementmentioning
confidence: 92%
“…An increase in total phenolic chemicals is responsible for higher antioxidant activity (Aronova et al, 2005). It was reported that important polyamines putrescine, spermidine, and spermine involved in controlling plants' antioxidant activity (Ahmad and Tahir, 2018).…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…Deficiency of zinc can affect plants negatively by stunting growth, stop tillering process, smaller leaves and their chlorosis, extending crop maturity period, sterility of spikelet and poor quality of harvested products [4]. [13] conducted an experiment to investigate impacts of biofortification of forage sorghum with zinc under different nitrogen levels. He reported that bio-fortification of zinc and nitrogen improved height of plant, leaf area, fresh forage yield, dry matter, protein content % and zinc content of plant but decreased the acid detergent fiber, neutral detergent fiber, and ash percentage.…”
Section: Role Of Zinc In Growth Of Crop Plantsmentioning
confidence: 99%